Szondi, Berman, and the Frühromantik movement: like a mémoire - Boccafogli, Lorenzo (2025)
In this article we present some lines of continuity between contemporary poetry, contemporary criticism and the study of the Frühromantik. Moreover, we make the theoretical assumptions common to Antoine Berman’s traductology and Peter Szondi’s material hermeneutics apparent.